Spermidine Revives Aged Sorghum Seed Germination by Boosting Antioxidant Defense - Yifan Xing; Huan Zhang; Chunjuan Liu; Chang Liu; Yufei Zhou (Antioxidants)
Seed aging has adverse effects on agricultural production, mainly because seed vigor is inhibited. Spermidine can improve seed vitality and germination ability to a certain extent and is essential for plant growth and plant response to stress. This study explored how spermidine counteracted aging effects on sorghum seed germination through antioxidant metabolism regulation. Aged seeds showed decreased vigor due to heightened reactive oxygen species (ROS) and diminished antioxidants. Applying spermidine notably enhanced aged seeds’ germination and vigor by boosting antioxidant enzyme activity and curbing ROS. Integrated transcriptomic, proteomic, and metabolomic analyses demonstrated that the majority of differentially expressed genes following exogenous spermidine treatment in aged sorghum seeds were significantly enriched in pathways related to glutathione metabolism, phenylpropanoid, and flavonoid biosynthesis, resulting in increased expression of genes encoding peroxidase, chalcone synthase, and glutathione s-transferase. Exogenous spermidine facilitated the synthesis of peroxidases and glutathione transferases. Analysis of flavonoid pathway intermediates showed a notable increase in antioxidant metabolites like isoquercitrin, underscoring their role in oxidative stress resistance. This multi-omics strategy underscores Spd’s role in boosting aged seeds’ antioxidants, highlighting the molecular basis of seed aging and Spd’s rejuvenating impact.